Using 2D site modelling and event water level data to quantify flow behaviours at road impediment sites in low gradient valley landscapes - Sarukkalige, Priyantha Ranjan; Farmer, D. (Engineers Australia, 2014)
Broad flat valley areas and locations dominated by low gradients are readily affected by flow impediments such as roads. These impediments can lead to water detention, flow backup, lateral inundation and additional flow distortions that introduce complexity to quantifying net channel flows and downstream water volumes. In many landscapes, particularly during moderate-large events, these sites are the only locations where data or anecdotal information can be collected and thus they form important input nodes and flow determination points in hydrologic and hydraulic models. Traditional small scale hydrology methods and 1D modelling often cannot be easily applied to the low gradient situation where flow energy gradients and flow direction can be highly variable. This paper details the use of ground data collection and 2D hydraulic modelling to carry out site-scale flow assessment of a raised road impediment within a low gradient, broad flat valley situation dominated by braided flows and multiple flow paths. The effect of the elevated roadway (culvert and floodway influences) is variously modelled for an observed event. This leads to assessment of the use of smallgrid2D modelling and anecdotal event information to estimate event flow behaviours through low gradient, water level sensitive impediment sites.